Tinjauan Hukum Islam Pada Praktik Pembulatan Timbangan Jasa Pengiriman Barang Jet & Tony (J&T) Express Cabang Sumoroto Ponorogo - Wulandari, Sekar; Nafi’ah, Nafi’ah; Wahyudi, Wahyudi (Journal of Sharia Economic Law, 2025)
The background to this research is that Ijarah is an agreement to transfer the right to use a good or service for a certain time through rental payments without being followed by a transfer of ownership of the right. J&T Express goods delivery service Sumoroto branch, where the admin is less transparent in providing information regarding rounding of scales, resulting in some consumers not knowing about this. This problem causes losses for consumers because the rounding carried out tends towards the top, and this final assignment contains the problem formulation (1) what is the practice of rounding the scales carried out at the Sumoroto branch of the J&T Express goods delivery service? , (2) how Islamic law reviews the practice of rounding scales at the J&T Express goods delivery service at the Sumoroto branch. This research uses a qualitative approach and uses observation, interview and documentation procedures. The conclusions are (1) the rounding method used by J&T Express Sumoroto branch is carried out by: Calculating actual weight scales (kilograms) with a weighing tolerance limit of 1.3 kg and scales based on the volume of goods (volumetric), (2) J&T Sumoroto Express Branch rounding practices are carried out with the ijarah system and is said to be valid because it fulfills the requirements and pillars of ijarah, including: aqid, Sighat, ujrah, and benefits. However, in the transactions carried out, the rounding system is not valid in Q.S Hud verse 85 because there is an element of rounding off the scales.